Enzymatic depolymerisation of cellulose - Pala, H. (2007)
Cellulose degree of polymerisation (DP) was determined in paper pulps and commercial powder celluloses before and after the enzymatic treatment with a blend of cellulases and hemicellulases. Three different methods were used: (i) chemical method, based on the measurement of the cellulose reducing power; (ii) viscosimetry; and (iii) gel permeation chromatography. Although based in very different principles, the three methods find similar DP values in the case of pure cellulose with narrow molecular weight distributions. The chemical method is more sensitive to detect enzymatic depolymerisation and appears to provide a good estimation of the number-average DP. GPC data offers more detailed information about the enzymes mode of action on the fibres, showing that cellulose hydrolysis in the presence of the commercial preparation Celluclast 1.5L follows a layer-by-layer solubilisation mechanism.